1973
DOI: 10.1017/s0016672300012970
|View full text |Cite
|
Sign up to set email alerts
|

Variability of recombination frequencies in theftrcistron ofCoprinusand its influence on the identification of marker effect alleles

Abstract: The variability of recombination frequencies between alleles of the ftr cistron is assessed and shown to be normally in the range of + 25 % though occasionally replicates differed by a factor of two and in rare cases even more extremely. It is shown that the variation results from biological differences between separate attempts at the same cross and cannot be ascribed to sampling error or any other controllable cause. In the light of this variability the marker effect alleles already recognized in this cistro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1975
1975
1980
1980

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Variations in interallelic recombination frequencies attributed to genetic background have previously been reported for Neurospora ( CATCHESIDE 1968;RAD-FORD 1968). Coprinus (MOORE 1973), and Zea mays (NELSON 1968;MOORE and CREECH 1972). Although particular genes which alter frequencies of intragenic recombination have been described in Neurospora ( JESSOP and CATCHESIDE 1965;SMITH 1965;JHA 1967) and Ascobolus (GIRARD and ROSSIGNOL 1974), the specific factors responsible for the variation among our strains are unknown at this time.…”
Section: Influence Of Strain Variability On Recombination Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in interallelic recombination frequencies attributed to genetic background have previously been reported for Neurospora ( CATCHESIDE 1968;RAD-FORD 1968). Coprinus (MOORE 1973), and Zea mays (NELSON 1968;MOORE and CREECH 1972). Although particular genes which alter frequencies of intragenic recombination have been described in Neurospora ( JESSOP and CATCHESIDE 1965;SMITH 1965;JHA 1967) and Ascobolus (GIRARD and ROSSIGNOL 1974), the specific factors responsible for the variation among our strains are unknown at this time.…”
Section: Influence Of Strain Variability On Recombination Ratesmentioning
confidence: 99%
“…Numerous studies with other organisms also have indicated the lack of strict correspondence between physical distances and recombination frequencies. Like the investigations with yeast discussed above, such disparities can be inferred where the order of the markers does not correspond to the order determined by deletion mapping (NORKIN 1970) or by purely genetic studies, where there are ambiguities in ordering markers (HOTCHKISS and EVANS 1958;HELINSKI and YANOFSKY 1962;KAPLAN, SUYAMA and BONNER 1962;RAVIN and IYER 1962;LOPER et al 1964;YANOFSKY et al 1964;TESSMAN 1965;LACKS 1966;MOUSSEAU 1966;FIELDS and OLIVE 1967;GRAY and EPHRUSSI-TAYLOR 1967;KRUSZEWSKA and GAJEWSKI 1967;MORSE and LERMAN 1969;PASZEWSKI and PRAZMO 1969;ROSSIGNOL 1969;GUTZ 1971;RONEN and SALTS 1971;JONES 1972;LEBLON and ROSSIGNOL 1973;MOORE 1973;STADLER and KARIYA 1973;and others). RONEN and SALTS (1971) found that frequencies of recombination between adjacent nucleotides varied 1 000-fold among 12 different sites in the bacteriophage T4rZZ gene.…”
Section: Influence Of Strain Variability On Recombination Ratesmentioning
confidence: 99%